Snake slough in birds' nests acts as a nest predator deterrent. Issue 6 (2nd November 2021) - Liu, Jinmei; Liang, Wei
Abstract : The use of snake slough as nest material by birds is considered an adaptive behavior to avoid nest predation. Here, we conducted predation experiments to test the hypothesis that the snake slough in nests of crested mynas ( Acridotheres cristatellus ) had anti-predatory effects. We put snake slough and white-rumped munia ( Lonchura striata ) eggs in the nest boxes to compare egg predation by Swinhoe's striped squirrels ( Tamiops swinhoei ), one of the main predators of cavity-nesting birds. In addition, we conducted experiments to examine if Swinhoe's striped squirrels identified the snake sloughs in the nest by vision or olfaction, and if the length of snake sloughs has effect on the predation rate. Our results showed that in the anti-predatory experiment, the egg predation rate (on days 3, 6) and the predation rate at which the squirrels first arrived the nest box were significantly lower in the experimental group than in the control group. In the olfaction experiment, there was no significant difference in both the predation rate (on days 1, 3, 6) and the predation rate at which the squirrels first arrived the nest box between the two groups. In the vision experiment, the predation rate at which the squirrels first arrived the nest box was significantly lower in the experimental group (hung snake slough) than in the control group (hung cotton strip). In the slough length experiment, the length of snake slough did not have a significant effect on the predation rate. These results suggest that the snake sloughs in bird nests can effectively deter nest predators, mainly via visual effect. Our study provided strong experimental evidence for the hypothesis that snake slough in birds' nests acts as a nest predator deterrent.